Kriging and dimension reduction techniques for delamination detection in composites using electrical resistance tomography. Issue 1 (2nd January 2023) - Díaz-Montiel, Paulina; Escalona-Galvis, Luis; Venkataraman, Satchi
Abstract : The electrical resistance tomography (ERT) is a non-destructive evaluation (NDE) technique that uses the inherent conductivity variations of composites to characterize internal damage. This article presents a study on the use of Kriging surrogate models for inverse identification of delamination in composites using ERT. Kriging surrogates are used to predict the change in electrical response of composites with delamination and matrix cracking damage. The results show that Kriging surrogates can successfully identify delamination even in the presence of matrix cracking. The technique demonstrated here that combines model order reduction with Kriging surrogates provides a computationally efficient and accurate method for damage identification using ERT.